2016
DOI: 10.1158/1078-0432.ccr-15-2443
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis–based Assessment of PD-L1 and Tumor-Associated Immune Cells Density Supports Distinct Intratumoral Microenvironment Groups in Non–small Cell Lung Carcinoma Patients

Abstract: Purpose We investigated the correlation between immunohistochemical PD-L1 expression and tumor-associated immune cells (TAICs) density in non–small cell lung carcinoma (NSCLC) and correlated them with clinicopathologic variables. Experimental Design Tumor tissue specimens from 254 stage I–III NSCLCs [146 adenocarcinomas; 108 squamous cell carcinomas (SCCs)] were examined. PD-L1 expression in malignant cells and macrophages and the density of TAICs expressing CD3, CD4, CD8, CD57, granzyme B, CD45RO, PD-1, FOX… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
115
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 46 publications
16
115
2
Order By: Relevance
“…In this regard, we documented that 36% of SCC samples displayed type III intrinsic induction, while in ADC the proportion of type IV and II was consistently higher (32% and 36%, respectively). Additionally, ADC displayed a lower expression of PD-L1 while, in line with other observations (26), the microenvironment seemed to be more chemoattractive for the overall population of T lymphocytes than in SCC. Accordingly, the clinical outcome of our cohort of surgically resected patients consistently varied between the two histotypes in terms of DFS that was considerably higher in SCC compared with ADC (28 months vs. 13 months, P < 0.001).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this regard, we documented that 36% of SCC samples displayed type III intrinsic induction, while in ADC the proportion of type IV and II was consistently higher (32% and 36%, respectively). Additionally, ADC displayed a lower expression of PD-L1 while, in line with other observations (26), the microenvironment seemed to be more chemoattractive for the overall population of T lymphocytes than in SCC. Accordingly, the clinical outcome of our cohort of surgically resected patients consistently varied between the two histotypes in terms of DFS that was considerably higher in SCC compared with ADC (28 months vs. 13 months, P < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…These cells are likely responsible for IFNg secretion, the most powerful PD-L1 stimulating factor (45). Secondly, KRAS mutation was associated with a reduced expression of PD-L1, as previously documented (44), while, at variance with the literature (26,46), EGFR mutation did not statistically impact on this parameter. It has been extensively reported that tumors with a greater mutational load could generate more neoantigens leading to a larger repertoire of tumor-specific T cells (41).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…New discoveries on the relationship between immune system and cancer have expanded the prospects of LC patient stratification by immune-markers, related to both tumour and the host's immunological status [4]. On the first side, tumour immune microenvironment (TIM) has proved to play a prognostic role in several solid tumours, including LC [5]. This is particularly true for new targeted therapies that modulate tumour-microenvironment cells, expressing programmed cell death protein 1 (PD-1) and its ligand (PD-L1), thereby achieving a substantial tumour regression and prolonged disease stabilisation also in LC patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These changes affect special T-cell populations by inducing tolerance to tumors, cause a high expression of inhibitory receptors and related ligands and suppressing T-cell activation which caused anti-tumor T-cells useless in tumor microenvironments. Thus, tumor cells are not recognized by adaptive immunity or innate immunity systems, and can avoid attack from the host immune system (Topalian et al, 2015;Parra et al, 2016). In an era when personalized medicine is strongly advocated in the field of oncology, the sheer diversity of cellular mutations that occur in different cancers poses a significant challenge to the personalization of cancer treatment.…”
Section: Preclinical Advances In Tumor Treatment Mechanisms and Pharmmentioning
confidence: 99%